Interdisciplinary homecare improves the mental health dimension of quality of life in diabetic ulcer patients - Wantonoro, Wantonoro; Komarudin, Komarudin; Imania, Dika Rizki; Harun, Sigit (Universitas 'Aisyiyah Yogyakarta, 2023)
The study aimed to identify the effect of interdisciplinary homecare programs on the mental health dimensions of patients' quality of life who require long-term care services. The research method was conducted with a quasi-experiment for six months of intervention on sixteen patients obtained with a random sample for January-September 2022 at the PKU Muhammadiyah Hospital Yogyakarta homecare unit. Short form-36 (SF-36) was used to evaluate the quality of life dimension. Results; Interdisciplinary homecare significantly improves the health of patients with long-term care needs; diabetic ulcers (p=0.001). Age and comorbidities were identified as characteristics of patients with diabetic ulcers, which must be considered in treating diabetic ulcers. Conclusion; Assistance with interdisciplinary home care is recommended in long-term care in community settings and patients to improve the quality of life, especially the mental health of patients.Â